Scolar, Mufti and Politician – Three “Lives” of Jakub Szynkiewicz - Usmanova, Diliara (Lietuvos istorijos studijos, 2023)
The article deals with the biography of the outstanding representative of the Polish-Lithuanian-Belarusian Tatar community – Jakub Szynkiewicz, whose life path fell on the first half of the 20th century, full of political upheavals and turning points. Being endowed by nature with great abilities, he left a significant mark in all areas and affairs in which he happened to be engaged. Both in the area of science and in the religious and administrative field, he achieved great success, leaving behind a significant legacy and a good memory. Perhaps only his political activity causes censure and various interpretations in modern literature, since it was based on the dubious basis of cooperation with a totalitarian, criminal regime. At the same time, this choice was partly predetermined by the political realities that dominated Eastern Europe at the turn of the 1930s and 1940s. In this article, the main attention is paid to the scholarly component of Jakub Szynkiewicz’s biography, which fell on the Berlin period of his life in the first half-mid-1920s. At the same time, it is reasonable to make a complete review of the main stages of his life, which allows one to enter the “scholarly” part in a broader historical context and show what caused this or that strategic choice of life trajectory, in which extremely sharp and fateful turns were sometimes made. Although Jakub Szynkiewicz never acted as an “armchair” scholar engaged in “pure science”, but rather was a quite politicized person. Nevertheless, his contribution to the world of Oriental studies is very significant and is associated both with the study of “kitabistics” and Turkological studies of the writings of Rabghuzi and other medieval texts. In general, scholarly activity should not be obscured by the religious-administrative or political actions of Jacub Szynkiewicz. Keywords: Jakub Szynkiewicz (Jakub Schinkewitsch), Polish-Lithuanian Tatars, University of Berlin, Oriental studies, Turkology, Rabghuzi’s work, Rzeczpospolita (The Polish-Lithuanian Commonwealth), Vilna, muftiate.